THE ROLE OF ACCOUNTING INFORMATION WRITING AND PROJECT IMPLEMENTATION - MIHAELA LESCONI FRUMUŞANU; ADELA BREUER; DOREL JURCHESCU (Annals of the University of Petrosani: Economics)
In this paper we try to clarify the term “project accounts, making an analysis of literature and legislation, that the documents underlying accessing structural funds (applicant's guides, toady of implementation). This scientific approach is structured in four chapters, the first two being a review of the literature, because the last part of the paper to present particular aspects of project accounting, emphasizing the role of accounting (accounting information) in writing and implementation of projects funded grant.